^Deviation of the emergent ray
Incident ray deviates clockwise towards the base at first face by amount δ1 (= i1 – r1) & then again deviates clockwise towards the base at second face by amount δ2 (= r2 – i2), thus the total deviation of the prism sum of δ1 & δ2 . Also from the cyclic quadilaternal AEHF,
r1 + i2 = A. From this information we can write
δ = δ1 + δ2 = i1 + r2 – A [Called Prism equation
For given μ, λ & A with the increase of incidence angle deviation angle first decreases & becomes minimum & then starts increasing as shown in the graph.